Evaluation of several ionic liquids for in situ hydrolysis of empty fruit bunches by locally-produced cellulase - Elgharbawy, A.A. (Springer Verlag, 2016)
Lignocellulosic biomasses, exhibit resistance to enzymatic hydrolysis due to the presence of lignin and hemicellulose. Ionic liquids proved their applicability in lignin degradation, however, ionic liquid removal has to be performed to proceed to hydrolysis. Therefore, this study reports an in situ hydrolysis of empty fruit bunches (EFB) that combined an ionic liquid (IL) pretreatment and enzymatic hydrolysis. For enzyme production, palm kernel cake (PKC) was used as the primary media for microbial cellulase (PKC-Cel) from Trichoderma reesei (RUTC30). The obtained enzyme exhibited a promising stability in several ionic liquids. Among few, in choline acetate ChoOAc, PKC-Cel retained 63.16Â % of the initial activity after 6Â h and lost only 10Â % of its activity in 10Â % IL/buffer mixture. Upon the confirmation of the PKC-Cel stability, EFB was subjected to IL-pretreatment followed by hydrolysis in a single step without further removal of the IL. The findings revealed that choline acetate ChoOAc and choline butyrate ChoBu were among the best ILs used in the study since 0.332Â Â±Â 0.05Â g glucose/g and 0.565Â Â±Â 0.08Â g total reducing sugar/g EFB were obtained after 24Â h of enzymatic hydrolysis. Compared to the untreated EFB, the amount of reducing sugar obtained after enzymatic hydrolysis increased by three-fold in the case of ChoOAc and ChoBu, two-fold with EMIMOAc and phosphate-based ILs whereas the lowest concentration was obtained in TBPHOAc. Pretreatment of EFB with ChoOAc and ChoBu showed significant differences in the morphology of EFB samples when observed with SEM. Analysis of the lignin, hemicellulose and hemicellulose showed that the total lignin content from the raw EFB was reduced from 37.8Â Â±Â 0.6 to 25.81Â Â±Â 0.35Â % (w/w) upon employment of ChoOAc in the compatible system. The PKC-Cel from T. reesei (RUTC30) exhibited promising characteristics that need to be investigated further towards a single-step process for bioethanol production. Â© 2016, The Author(s).